Evaluation d’un dispositif d’ePortfolio universitaire en archéologie et histoire de l’art - Laurent Verslype; Julie Lecoq; Pascale Corten-Gualtieri; Emmanuelle Druart (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
The department of Archaeology and History of Art of the University of Louvain, Louvain-la-Neuve (UCL) established a self-directed learning project for its bachelor degree. The project is based on the commitment of each student in cultural and patrimonial activities. The students must report in a critical and reflexive way in an electronic portfolio which is gradualy and formatively assessed. At the end of the three years of the university degree, the portfolio is summatively assessed.After two years of implementation, the entire process has been surveyed. The results show that the modalities of supervision and evaluation contribute significantly to the learning of several core-competencies in university education: the ability to analyse, criticize and synthetize the information, to bring in appropriate arguments, and their skill to write universitary quality reports. However, the progress achieved in terms of autonomy and reflective capacity is more mixed in the population of surveyed students.